A call to focus on farmer intuition for improved management decision-making. (December 2020) - von Diest, Saskia G; Wright, Julia; Samways, Michael J; Kieft, Henk
Mainstream agricultural research takes a rational approach to generate empirical, tangible knowledge for increased yields and sustainability. This approach has led to the development of technological tools to support farmers in their management decision-making, which, while helpful, are not able to factor in the complex, dynamic variables that motivate farmer decision-making. More importantly, farmers often do not adopt these tools as expected. Could a solution lie in considering other sources and types of agricultural knowledge? Some farmers report relying largely on intuition (knowing from within) to inform their practical management decisions, resulting in both qualitative and quantitative benefits. Intuition allows access to valuable tacit (informal, intangible) knowledge, which can be used to explore and apply more resilient agricultural practices. It is an immediate and valuable part of decision-making, and deserves more attention from both farmers and researchers. This paper discusses potential advantages, challenges to, and methods of mainstreaming farmer intuition, and presents appropriate methodologies for its development, emphasizing the need to expand the underlying ontology and epistemology of the mainstream scientific community.